Narrative intervention in school-aged children with autism spectrum disorder: a systematic review. (2nd October 2022) - Tam, Joyce Yuen Ching; Barrett, Elizabeth Ann; Ho, Astrid Yuen Hin
ABSTRACT: This review evaluated the evidence for narrative intervention on language and pragmatic outcomes for school-aged children with autism spectrum disorder (ASD). The study protocol for this review followed the PRISMA-Protocol checklist and was pre-registered on Open Science Framework. Ten electronic databases were searched to identify experimental designs studies that targeted school-aged children aged 5–18 with ASD. Two independent reviewers evaluated the inclusion eligibility of full-text studies. All included studies were critically appraised by two independent reviewers. Data were coded for study characteristics and outcomes of interest. Results from different outcome measures were synthesized qualitatively. The report was reviewed with the PRISMA checklist to ensure complete reporting. Forty participants from seven studies were included in this review. Six single-case experimental design studies and one group study were included. All these studies included methodological flaws that reduced the strength of evidence. The results indicated that narrative intervention might have large effects on comprehension of discourse, medium effects on production of macrostructure and microstructure, and small effects on pragmatic skills compared to pretreatment. For maintenance effects and other outcome constructs, including pragmatic skills, it was inconclusive whether the narrative intervention had true effects. Evidence from this review suggests that narrative intervention may produce medium-size effects on several constructs of language outcomes. Nonetheless, there was no evidence that showed those gains could be maintained post-treatment. The methodological weaknesses and the small sample of included studies restrict stronger conclusions from being drawn. More high-quality group studies with clearly described treatment procedures are needed.